Analisis Tingkat Kesiapan Keamanan Informasi Menggunakan Indeks KAMI (Keamanan Informasi) 4.0 (Studi Kasus : Dinas Komunikasi dan Informatika Provinsi Jawa Timur) - Gede Dandy Salodivansa Barani; Widhy Hayuhardhika Nugraha Putra; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The Communication and informatics Agency of East Java is a government agency that organize communication dan informatics, statistics and encryption or security fields. Information security is a key in securing informations, hence The Ministry of Communication dan Informatics issued Information Security Management System related regulation on government agencies in Indonesia Minister of Communication and Informatic regulation number 4 of 2016, hence the Communication and Informatics Agency of East Java Province as the communication and informatics executor need to evaluate and analyze their information security. In this study, evaluation and analysis conducted using KAMI (Keamanan Informasi) Index questionnaires to determine the maturity and completeness level of information secutiry on six areas such as governance, risk management, frameworks, assets management, technology and information security, and supplement. From the evaluation, the maturity level on five areas are between level I to II and the completeness level gets a score of 258. With these score and levels, The Communication and Informatics Agency of East Java determined needs improvements to conduct with ISO27001 sertification. The result of the analysis form basis of recommendations obtained from ISO2700 control, one of the recommendations is information security regulations related to A.5.1.1 control of ISO27001.